2015
DOI: 10.1007/s12152-015-9235-6
|View full text |Cite
|
Sign up to set email alerts
|

Can’t We All Disagree More Constructively? Moral Foundations, Moral Reasoning, and Political Disagreement

Abstract: Can't we all disagree more constructively?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Therefore, the effects of moralising a disagreement on the right to secede instead of fostering more stability and order (a very liberal and realist concern) promote moral entrenchment and social division. Empirical research has consistently found that deepening the moral foundations of political disagreements makes political debates harder to develop (Sauer ; Valentini ).…”
Section: Realism and Moral Political Philosophy On Secessionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effects of moralising a disagreement on the right to secede instead of fostering more stability and order (a very liberal and realist concern) promote moral entrenchment and social division. Empirical research has consistently found that deepening the moral foundations of political disagreements makes political debates harder to develop (Sauer ; Valentini ).…”
Section: Realism and Moral Political Philosophy On Secessionmentioning
confidence: 99%
“…Therefore, the effects of moralising a disagreement on the right to secede instead of fostering more stability and order (a very liberal and realist concern) promote moral entrenchment and social division. Empirical research has consistently found that deepening the moral foundations of political disagreements makes political debates harder to develop (Sauer ; Valentini ).We also know the potential violence associated with secession conflicts (Coggins ; Sorens ). Territorial demands are at the heart of an important number of civil wars around the world, and it is not necessary to restate just how explosive these conflicts tend to be (Toft ).…”
Section: Realism and Moral Political Philosophy On Secessionmentioning
confidence: 99%
“…Virtually everyone is at least somewhat sensitive to the moral relevance of all six foundations, even though different people – and, in particular, different political groups – assign more (or less) importance to different foundations. Liberals famously emphasize the first two foundations at the expense of the others; conservatives have a more balanced appreciation of all six foundations (Sauer, ). This, however, does not support moral relativism; it merely explains why there are differences between basic political outlooks such as liberalism and conservatism.…”
Section: Evidence For Agreementmentioning
confidence: 99%
“…Liberals famously emphasize the first two foundations at the expense of the others; conservatives have a more balanced appreciation of all six foundations (Sauer, 2015). This, however, does not support moral relativism; it merely explains why there are differences between basic political outlooks such as liberalism and conservatism.…”
Section: Liberty/oppression 12mentioning
confidence: 99%
“…Moral judgment, it now seemed, is not just largely intuitive, but which intuitions people have is due to differences in their moral foundations , with important political consequences (Graham, Haidt, & Nosek, 2009;Iyer, Koleva, Graham, Ditto, & Haidt, 2012;cf. Curry, 2016, Sauer, 2015.…”
Section: The Anti-rationalist Turnmentioning
confidence: 99%